Assessing the evolution of the Aleppo Pine plantations by using field measurements and one-way Analysis of variance - Khaouani, Boumediene; Hirche, Azziz; Bourfa, Said; Berrabeh, Djamaledine; Hadbaoui, Ilyes; Youb, Okkacha; Derdour, Abdessamed (Technium Social Sciences Journal, 2022)
Moudjbara area considered a gateway to Algeria's Great Sahara, was the first perimeter to be afforested with Aleppo pine in 1972 as part of a green dam initiative to combat desertification and preserve soil from wind erosion. This study examines the evolution of the species Pinus Halepensis Mill commonly known as the Aleppo pine in the Moudjbara plantations by comparing it to that of the natural forest of the Djellal Mountains in the Chergui region. Several field surveys were conducted, and four sites were selected in the natural forest and four sites in the Moudjbara afforestation. In each site, we performed 50 dendrometric measurements with 200 tree stakes. The selection is based on information on regeneration and plant quality. Stations are classified into four categories namely station of good regeneration, station slightly well regenerated, station moderately regenerated, and station of weak regeneration, which allow us to have primary reference data and to make a reliable assessment of the behavior of Aleppo pine in the Green Dam. The attribute ranking obtained from the ANOVA approximation provides us with crucial information of comparison between the natural forest and the reforestation zone. The results obtained can be used to adjust the planting density, rigorously choose the species, and adapt the soil preparation and planting techniques.